2015
DOI: 10.1016/j.jhydrol.2015.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Vadose zone oxygen (O2) dynamics during drying and wetting cycles: An artificial recharge laboratory experiment

Abstract: 10Vadose zone oxygen dynamics control all subsurface redox reactions and play a decisive role in 11 maintaining groundwater quality. Although drying and wetting events are common in artificial 12 recharge, their effects on subsurface oxygen distribution are poorly documented. We monitored 13 oxygen concentration in the unsaturated zone in a mid-scale (1 m high) laboratory soil lysimeter, 14which was subjected to short wetting and drying cycles that simulated a highly permeable 38• Surface scraping results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 32 publications
3
38
0
Order By: Relevance
“…Substrate oxidation reduction potential (ORP) and/or oxygen concentration decreased with depth because the oxygen from air diffused to the substrate was limited in non-aerated rapid infiltration system and SWIS (Dutta et al, 2015;Wang et al, 2010;Zhang et al, 2005). However, substrate ORP results still showed that aerobic conditions in the upper layer and anoxic or anaerobic conditions in the subsequent sections were well developed in a SWIS with continuous feed and intermittent aeration.…”
Section: Effect Of Intermittent Aerationmentioning
confidence: 99%
“…Substrate oxidation reduction potential (ORP) and/or oxygen concentration decreased with depth because the oxygen from air diffused to the substrate was limited in non-aerated rapid infiltration system and SWIS (Dutta et al, 2015;Wang et al, 2010;Zhang et al, 2005). However, substrate ORP results still showed that aerobic conditions in the upper layer and anoxic or anaerobic conditions in the subsequent sections were well developed in a SWIS with continuous feed and intermittent aeration.…”
Section: Effect Of Intermittent Aerationmentioning
confidence: 99%
“…Laboratory experiments and constructed wetlands demonstrate that concentration of microbial activity and TOC degradation is concentrated in the first centimeters of the filter material (Ragusa et al, 2004;Sleytr et al, 2007;Tietz et al, 2007) in response to oxygen concentration vertical distribution. Although rapid oxygen depletion and consequent denitrification conditions have been evidenced in lab-scale MAR experiments (Alidina et al, 2014a;Dutta et al, 2015), this effect may not happen 10 rapidly under real infiltration conditions, where entrapped gas (Heilweil et al, 2004) or fingering processes (Kung, 1990) may provide higher oxygen concentrations than in lower dimension systems (e.g., columns). Lab-experiments are doubtlessly useful to elucidate the behavior of microbial communities under controlled conditions.…”
mentioning
confidence: 99%
“…Whereas investigations on pollution of the aquifer in up-flow direction in water-saturated soil in the meter-scale in a lysimeter have been reported over a period of 84 days [45], [16] to our knowledge no long-term horizontal flow experiments of groundwater in this scale under defined conditions are available. Thus we performed three-dimensional long-term horizontal flow-through experiments in an instrumented stainless steel container (SSC) of lysimeter size through well-defined quartz sand and its CF.…”
Section: Introductionmentioning
confidence: 98%
“…Drying cycles allowed re-saturation of the soil with oxygen even in the depth, and after re-wetting the growth of microorganism in the biofilm on soil particles was continuing, indicating survival of the bacteria in the biofilm. This led to further decreasing infiltration rates [16] and may finally cause biological clogging. First attention of bacterial biofilm formation came from medicine, when microorganisms growing in or forming mucous surfaces were recognized as a common cause of persistent infections [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation